Antinociceptive effects of the 6-O-sulfate ester of morphine in normal and diabetic rats: Comparative role of mu- and delta-opioid receptors. (November 2016) - Yadlapalli, Jai Shankar K.; Ford, Benjamin M.; Ketkar, Amit; Wan, Anqi; Penthala, Narasimha R.; Eoff, Robert L.; Prather, Paul L.; Dobretsov, Maxim; Crooks, Peter A.
Graphical abstract: In vivo analysis of morphine- and M6S-induced (i.p.) antinociception was examined by hot water tail flick latency test in naive and diabetic rats. In vitro experiments to determine opioid receptor affinity and activation of post-receptor events utilized Chinese hamster ovary (CHO) cells transfected with human mu- or delta-ORs. M6S produced more potent antinociception than morphine in both naïve and diabetic rats. The data imply that the improved analgesic and tolerance profile of M6S over morphine may be due to the ability of M6S to act at both mu- and delta-ORs. Abstract: This study determined the antinociceptive effects of morphine and morphine-6- O -sulfate (M6S) in both normal and diabetic rats, and evaluated the comparative role of mu-opioid receptors (mu-ORs) and delta-opioid receptors (delta-ORs) in the antinociceptive action of these opioids. In vitro characterization of mu-OR and delta-OR-mediated signaling by M6S and morphine in stably transfected Chinese hamster ovary (CHO-K1) cells showed that M6S exhibited a 6-fold higher affinity for delta-ORs and modulated G-protein and adenylyl cyclase activity via delta-ORs more potently than morphine. Interestingly, while morphine acted as a full agonist at delta-ORs in both functional assays examined, M6S exhibited either partial or full agonist activity for modulation of G-protein or adenylyl cyclase activity, respectively. Molecular docking studies indicated that M6S but not morphine binds equally well at the ligand binding site of both mu- and delta-ORs. In vivo analgesic effects of M6S and morphine in both normal and streptozotocin-induced diabetic Sprague-Dawley rats utilizing the hot water tail flick latency test showed that M6S produced more potent antinociception than morphine in both normal rats and diabetic rats. This difference in potency was abrogated following antagonism of delta- but not mu- or kappa (kappa-ORs) opioid receptors. During 9 days of chronic treatment, tolerance developed to morphine-treated but not to M6S-treated rats. Rats that developed tolerance to morphine still remained responsive to M6S. Collectively, this study demonstrates that M6S is a potent and efficacious mu/delta opioid analgesic with a delayed tolerance profile when compared to morphine in both normal and diabetic rats. Perspective: This study demonstrates that M6S acts at both mu- and delta-ORs, and adds to the growing evidence that the use of mixed mu/delta opioid agonists in pain treatment may have clinical benefit.